Upaya Peningkatan Penjualan Terhadap Produk UMKM “Mama Ni” Yang Tersedia Di Transmart Rungkut - Sasmianingtias, Ririn; Nirawati, Lia (Universitas Gajah Putih, Indonesia, 2023)
Empowerment of Micro, Small and Medium Enterprises in the midst of globalization and high competition requires that this form of business be able to face global challenges, such as increasing product and service innovation, developing human and technological resources, and expanding marketing areas. This research uses qualitative methods so that the research process can be adapted to the facts encountered in the field when conducting research. Implementation of displays or good arrangement of goods can attract consumers' attention and help them to easily observe the items on display and finally buy these items.